Modelo de hemiparkinsonismo por 6-hidroxidopamina em primatas Sapajus apella: características comportamentais e histológicas - PEDROSA, Laís Resque Russo (Universidade Federal do Pará, 2025)
Despite considerable side effects and decreasing effectiveness over time, the treatment for Parkinson's disease (PD) has remained largely unchanged for over 50 years. However, several aspects of the disease's pathophysiology remain poorly understood. The development of new therapies and the elucidation of mechanisms related to the disease are among the biggest current challenges in neuroscience research. In this context, non-human primate (NHP) experimental models are particularly relevant due to their high phylogenetic proximity, encephalization rate, and complex motor and behavioral repertoire, confer high predictive power for clinical outcomes. The 6-hydroxydopamine inoculation model of parkinsonism mimics relevant features of PD and may represent an important experimental refinement in primates. The present study aimed to develop a model of hemiparkinsonism induction in Sapajus apella primates, characterizing the behavioral and histological aspects. For this purpose, adult male Sapajus apella monkeys were subjected to motor tests to observe motor performance before and after unilateral injection of 6-OHDA in the nigrostriatal pathways at concentrations of 4 (N=1), 10 (N=1) and 40 (N=1) mg/μl in the dominant hemisphere. As a surgical control (N=1), one animal underwent surgery containing only solvent. Stereotaxic coordinates for the 12 6-OHDA inoculation sites were calculated based on individual Magnetic Resonance Imaging (MRI) images. Immunohistochemistry for tyrosine hydroxylase (TH) was performed on 50 μm coronal sections of the midbrain. As a statistical analysis, two-way ANOVA was used to verify possible differences in behavioral parameters and neuronal exclusion between groups, considering the dominant (therefore affected) and non-dominant hemispheres. There were significant changes in motor patterns of dominance and manual preference after surgical intervention. 6-OHDA induction in the nigrostriatal pathways appears to be a good method of inducing parkinsonism with the induction of detectable symptoms in primates.